Out-of-Pocket Payments for Delivery Care in India: Do Households face Hardship Financing?. (June 2021) - Yadav, Jeetendra; John, Denny; Menon, Geetha R.; Allarakha, Shaziya
Background: Present study aims to examine the socioeconomic and demographic factors that affect health care utilization, health care expenditure and financing strategies for delivery care in India. Methods: The study uses data from National Family Health Survey (NFHS-4), 2015-2016. Descriptive, bivariate and multivariate regression analysis were carried out to examine health care utilization, out of pocket expenditure and financing strategies for delivery care in India. We used hardship financing as when people resort to borrowings, or sale of property/jewelry to pay for healthcare expenditure Results: Overall, Janani Suraksha Yojana (JSY) could cover less than 40% of the delivery care expenditure across all states. One-third of the households borrowed money or sold property/jewelry for delivery care expenditure. Highest exposure to hardship financing was observed in utilisation of private healthcare facilities for delivery. Women from the higher income quintiles are less likely to experience hardship financing as compared to women from the poorest wealth quintile. Conclusions: The study results will be useful for government to ensure that financing policies for delivery such as JSY are effective to provide availability and affordability of delivery healthcare in India.